2003
DOI: 10.1046/j.1365-313x.2003.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

Global expression profiling of sulfur‐starved Arabidopsis by DNA macroarray reveals the role of O‐acetyl‐l‐serine as a general regulator of gene expression in response to sulfur nutrition

Abstract: SummaryTo investigate the changes in profiles of mRNA accumulation in response to sulfur deficiency, approximately 13 000 non-redundant Arabidopsis thaliana ESTs corresponding to approximately 9000 genes were analyzed using DNA macroarray. Three-week-old Arabidopsis plants grown on an agarose-solidified control medium were transferred to a sulfate-free medium and grown for 48 h for the analyses of sulfur-related metabolites and global gene expression profiles. Concentrations of sulfate, O-acetyl-L-serine (OAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
308
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(339 citation statements)
references
References 49 publications
25
308
0
6
Order By: Relevance
“…The contents of O-acetyl-L-serine (17) increased significantly in sulfur-deficient Arabidopsis seedlings, consistent with earlier reports (Nikiforova et al, 2003(Nikiforova et al, , 2005. Under short-term sulfur deficiency or with exogenous supplementation of O-acetyl-L-serine (17), the endogenous content of O-acetyl-L-serine (17) increased significantly in both leaves and roots of Arabidopsis (Hirai et al, 2003). Under sulfur deficiency, the decreased levels of cysteine resulted in the accumulation of its upstream metabolites, namely O-acetyl-L-serine (17), serine (19) and glycine (27) (Nikiforova et al, 2005).…”
Section: Comparison Of Metabolite Profiles Obtained With Gc-tof-mssupporting
confidence: 89%
See 1 more Smart Citation
“…The contents of O-acetyl-L-serine (17) increased significantly in sulfur-deficient Arabidopsis seedlings, consistent with earlier reports (Nikiforova et al, 2003(Nikiforova et al, , 2005. Under short-term sulfur deficiency or with exogenous supplementation of O-acetyl-L-serine (17), the endogenous content of O-acetyl-L-serine (17) increased significantly in both leaves and roots of Arabidopsis (Hirai et al, 2003). Under sulfur deficiency, the decreased levels of cysteine resulted in the accumulation of its upstream metabolites, namely O-acetyl-L-serine (17), serine (19) and glycine (27) (Nikiforova et al, 2005).…”
Section: Comparison Of Metabolite Profiles Obtained With Gc-tof-mssupporting
confidence: 89%
“…Herein, however, it was demonstrated that the levels of galactinol (45) were elevated in response to sinalbin (1) supplementation only. O-Acetyl-L-serine (17) is a general regulator of gene expression associated with sulfur nutrition (Hirai et al, 2003). The contents of O-acetyl-L-serine (17) increased significantly in sulfur-deficient Arabidopsis seedlings, consistent with earlier reports (Nikiforova et al, 2003(Nikiforova et al, , 2005.…”
Section: Comparison Of Metabolite Profiles Obtained With Gc-tof-mssupporting
confidence: 86%
“…Col-0 appears to also be better able to maintain a sufficiently large pool of reduced S compounds, especially glutathione, when treated with selenite, which may in part be responsible for its resistance. Incidentally, a reduction in GSH content was also observed in S-starved Arabidopsis (Hirai et al, 2003), indicating that selenite treatment induced S starvation in Ws-2 plants.…”
Section: Resultsmentioning
confidence: 92%
“…In view of the finding that both ethylene and JA appear to play important roles in selenite resistance in Arabidopsis, it is interesting to note that in earlier studies JA was implicated to be involved in the regulation of S metabolism because S starvation induced genes involved in JA synthesis, as well as JA-responsive genes (Hirai et al, 2003;Maruyama-Nakashita et al, 2003;Nikiforova et al, 2003). The above-mentioned studies showed no indication that ethylene plays a role in S deficiency responses.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation